Au cœur de la mort : faire science avec les défunts - Marc-Antoine Berthod (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Ever since the founding of anthropology as a discipline, the theme of death has nourished an abundant literature that puts into perspective the ways in which communities construct boundaries between the living and the dead: how they define intervals between the two categories while designating places reserved for the deceased. In this text, we first discuss how these boundaries and their transgressions have been considered by cultural and social anthropologists. We then suggest that a shift has occurred in perspectives on these aspects, through a commentary on the notion of techno-scientific immortalism and the emergence of certain ecological funeral practices. In parallel, we show the methodological importance of being present at the time of a passage from life to death, in this case at the time of an assisted suicide, in order to document how this boundary between life and death is established. Through these two illustrations, the aim is to bring the questions raised by cultural and social anthropologists into perspective with questions liable to be encountered by biological anthropologists and funerary archaeology when interpreting the relationship between the living and the dead over historical time.